The Mediatization Of Leadership: Grassroots Digital Facilitators As Organic Intellectuals - Felt, Mylynn; Bakardjieva, Maria; Dumitrica, Delia (AoIR Selected Papers of Internet Research, 2017)
Whether due to an organizational shift to networks over bureaucracies or due to a change in values, many social movements in the current protest cycle are not characterized by visible leadership. This paper undertakes an in-depth analysis of data obtained through interviews, observations and analysis of media content related to three Canadian cases of civic mobilization of different scale, all of which strategically employed social media: the provincial MLA Playdate, the national Murdered and Missing Indigenous Women campaign, and the Canadian response to the international Refugees Welcome movement. What attributes, competencies, skills, and practices distinguished the individuals and groups that played key roles in the inception and ongoing organization of these movements? How can their role (or roles) be defined, if not as traditional organizational leadership? The paper uses Gramsci’s notion of the “organic intellectual” and Bourdieu’s (1991) model of the “political field” to propose a conceptual framework for understanding the role of these organizers as political discourse-producers, sociometric stars and organic intellectuals. Ultimately, the organizers of the mobilizations under study were successful in infiltrating the political field, typically the domain of institutional players, with discourses collaboratively produced in the exchanges among grassroots citizens. By looking closely at the three cases through the lenses offered by these concepts, we identify the specific competencies, strategies and styles that characterize mediatized civic leadership.